One-Stage Off-Pump Transapical Mitral Valve Repair and Aortic Valve Replacement. Issue 19 (12th May 2015) - Gerosa, Gino; D'Onofrio, Augusto; Manzan, Erica; Besola, Laura; Bizzotto, Eleonora; Zucchetta, Fabio; Tarantini, Giuseppe; Pittarello, Demetrio; Colli, Andrea
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.